Stratigraphic and Structural Study of Khlesia Region Using 2D Seismic Data - North Western Iraq - Al-Ridha, Nawal A.; Al-Khafaji, Hassan J. (Iraqi Journal of Science, 2019)
This study deals with interpretation of stratigraphic and structural of Khlesia area north-west Iraq in Nineveh province, near the Iraq- Syria border, by using 2D seismic data. Synthetic trace are prepared by using available data of the well (Kh-1) using Geoframe program to define and picking the reflectors on seismic section. These reflectors are: (Within Fatha and Kurra Chine reflectors) representing Middle Miocene and Late Triassic ages respectively. A listric growth normal fault is affecting the stratigraphic succession, and normal fault as a result of collision of Arabian plate with Eurasian plate. In addition, minor normal faults (Dendritic and Tension) are developed on the listric normal growth fault and influenced the studied reflectors, the fault system extends (NE-SW) direction. The structural interpretation result shows two grabens (Khlesia and Tayarat) and number of structures domes. Seismic interpretation of the study area confirms the existence of some stratigraphic features which are probable to be hydrocarbon traps. Application of seismic attributes (instantaneous phase, instantaneous frequency and reflection strength section) showed low values in frequency and reflection strength, these values reflect or indicate to presence of hydrocarbon areas.